Determinants and perception of postpartum intrauterine contraceptive device services in Maharashtra, India - Jayashree Sachin Gothankar; Prakash Doke; Prasad Pore; Arvinder Pal Singh Narula; Sudhanshu Mahajan; Rupesh Kumar Deshmukh (International Journal of Public Health Science (IJPHS), 2022)
Undesired and unintended pregnancies increase unwanted births or induced abortions, consequently increasing maternal morbidity and mortality. Postpartum insertion of the Intra Uterine Contraceptive Device (PPIUCD) is an effective method for population control. The authors conducted the study to assess the determinants of PPIUCD services by identifying beneficiaries and healthcare workers' perceptions. We conducted this study in Maharashtra State, India having five geographical divisions and 36 districts. The authors visited 10 Primary Health Centers and three Community Health Centers from five districts, randomly selecting one from each division. We interviewed 45 women who had undergone insertion one day to one year prior and 17 health care workers. About one-third of women received counseling during pregnancy. The medical officers obtained the consents mostly during delivery. They inserted about 85% of devices within one hour of delivery. About 38% of women had at least one complication. Lower abdominal pain (22.22%), irregular bleeding (20.00%), the expulsion of CuT (13.33%), pain during periods (13.33%) were common. The removal rate was 6.67%. The complication rates observed in the present study are comparable to the hospital studies. Thus, the study reassures that the services in small institutions are very safe, and governments can fearlessly implement the program.Keywords: ComplicationsCounselingExpulsionHealth center Quality Removal